Maternal mortality ratio in China from 1990 to 2019: trends, causes and correlations - Lu Chen; Penghui Feng; Lance Shaver; Zengwu Wang (BMC, 2021)
Abstract Background Maternal mortality ratio is an important indicator to evaluate the health status in developing countries. Previous studies on maternal mortality ratio in China were limited to certain areas or short periods of time, and there was a lack of research on correlations with public health funding. This study aimed to assess the trends in the maternal mortality ratio, the causes of maternal death, and the correlations between maternal mortality ratio and total health financing composition in China from 1990 to 2019. Methods Data in this longitudinal study were collected from the China Health Statistics Yearbooks (1991-2020) and China Statistical Yearbook 2020. Linear regression analysis was used to assess the trends in the maternal mortality ratio in China. Pearson correlation analysis was used to assess the correlations between national maternal mortality ratio and total health financing composition. Results The yearly trends of the national, rural and urban maternal mortality ratio were − 2.290 (p < 0.01), − 3.167 (p < 0.01), and − 0.901 (p < 0.01), respectively. The gap in maternal mortality ratio between urban and rural areas has narrowed. Obstetric hemorrhage was the leading cause of maternal death. The mortalities ratios for the main causes of maternal death all decreased in China from 1990 to 2019. The hospital delivery rate in China increased, with almost all pregnant women giving birth in hospitals in 2019. Government health expenditure as a proportion of total health expenditure was negatively correlated with the maternal mortality ratio (r = − 0.667, p < 0.01), and out-of-pocket health expenditure as a proportion of total health expenditure was positively correlated with the maternal mortality ratio (r = 0.516, p < 0.01). Conclusion China has made remarkable progress in improving maternal survival, especially in rural areas. The maternal mortality ratio in China showed a downward trend over time. To further reduce the maternal mortality ratio, China should take effective measures to prevent obstetric hemorrhage, increase the quality of obstetric care, improve the efficiency and fairness of the government health funding, reduce income inequality, and strengthen the medical security system.